O uso do poder de compra do estado como instrumento de política pública: a lei complementar nº 123/2006, sua implementação - Silva, Erivam Paulo da (2008)
This study aims to bring back the debate on the use of the purchasing power of the State as instrument to boost other public policies established by federal entities. Besides putting it in a context of innovation in the public sector, the study of this issue must consider all its variables and questions, whwther of legal, economic, social or political order, starting with the one I consider the most important: the possibility of the State to assert its power of puchasing in order to design and promote markets, searching to achieve other objectives rather than those traditionally accepted. Thus, in the analysis of a direct application of a new practice, this study evaluates the implementation of the Additional Law number 123/06, which gives a differentiating treatment to micro and small enterprises in public contracting. By means of interviews, information was collected with the relevant actors in in this phase. The conclusion was that aspects such as the heterogeneity of the segment of the MPE`s and their low capacity of articulation, along with the endogenous obstacles of the instituion of the bidding, contribute decively to the low stage of the implementation that occurs at this moment.